2021
DOI: 10.1051/0004-6361/202039872
|View full text |Cite
|
Sign up to set email alerts
|

The near-Sun streamer belt solar wind: turbulence and solar wind acceleration

Abstract: The fourth orbit of Parker Solar Probe (PSP) reached heliocentric distances down to 27.9 R , allowing solar wind turbulence and acceleration mechanisms to be studied in situ closer to the Sun than previously possible. The turbulence properties were found to be significantly different in the inbound and outbound portions of PSP's fourth solar encounter, which was likely due to the proximity to the heliospheric current sheet (HCS) in the outbound period. Near the HCS, in the streamer belt wind, the turbulence wa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 75 publications
8
18
0
Order By: Relevance
“…4). This is consistent with the scaling of non-HPS solar wind previously shown by Chen et al (2021) using a similar encounter 4 stream. The f −3/2 power law is also consistent with solar wind from the small equatorial coronal hole in encounter 1 (Bale et al 2019;Chen et al 2020).…”
Section: Type Of Solar Wind and Source Regionsupporting
confidence: 91%
See 1 more Smart Citation
“…4). This is consistent with the scaling of non-HPS solar wind previously shown by Chen et al (2021) using a similar encounter 4 stream. The f −3/2 power law is also consistent with solar wind from the small equatorial coronal hole in encounter 1 (Bale et al 2019;Chen et al 2020).…”
Section: Type Of Solar Wind and Source Regionsupporting
confidence: 91%
“…The f −3/2 power law is also consistent with solar wind from the small equatorial coronal hole in encounter 1 (Bale et al 2019;Chen et al 2020). Conversely, the wind measured during the outbound sections of the encounters has an inertial range power law of f −5/3 (Chen et al 2021). The wind during this time was slower and more dense, consistent with predominantly HPS wind.…”
Section: Type Of Solar Wind and Source Regionsupporting
confidence: 64%
“…Power spectra of the magnetic field fluctuations for each stream show power laws of -3/2 in the inertial range (not shown here). This is consistent with the scaling of non-HPS solar wind previously shown by Chen et al (2021) using a similar encounter 4 stream. The -3/2 power law is also consistent with solar wind from the small equatorial coronal hole in encounter 1 (Bale et al 2019;Chen et al 2020).…”
Section: Type Of Solar Wind and Source Regionsupporting
confidence: 91%
“…Similarly, (Chen et al, 2020) showed that turbulence evolves between 0.17 and 1 AU: at 0.17 AU the data showed increased energy spectral density, a slope of −3/2, lower magnetic compressibility, and increased relative amount of outward propagating Alfvénic fluctuations compared to inward. Close to the Sun, both the magnetic field and velocity spectra have a slope of −3/2, but only the magnetic spectra is observed to steepen with distance, and the outward dominance of the Alfvénic fluctuations is observed to decrease with distance (Chen et al, 2021;Shi et al, 2021). The evolution of the outward wave dominance as well as the evolution of the spectral break point with distance is supported by MHD simulations of turbulence (Roberts et al, 1991).…”
Section: Turbulent Structuring In the Solar Windmentioning
confidence: 76%
“…In the fast wind, this break point occurs near 10 mHz at 0.3 AU and steadily evolves to lower frequencies at larger distances of less than 0.1 mHz at 4.8 AU (Bruno et al, 2009;Bruno and Carbone, 2013). Those results also showed that the slow wind is not observed to have a corresponding break between the inertial and energy containing scales, but more recent results with Parker Solar Probe show that the slow wind has a break to energy containing scales, but at a lower frequency than the fast wind (Chen et al, 2021).…”
Section: Turbulent Structuring In the Solar Windmentioning
confidence: 78%